Avaliação das propriedades mecânicas do aço inoxidável duplex UNS S32304 submetido à soldagem TIG e diferentes temperaturas de tratamento térmico - Caetano, Gabriela Aksascki (2019)
The duplex stainless steel UNS S32304 has been investigated as a candidate for external construction of areceptacle for transporting radioactive material associated with the future Brazilian Multipurpose Nuclear Reactor(RMB), as it presents the combination of excellent mechanical properties and high resistance to corrosion, as a consequence of its ferritic-austenitic biphasic structure.The outer shell construction of this receptacle provides for the use of welded UNS S32304 steel sheets.In order to evaluate the effect of post-weld heat treatments on the mechanical properties and to guarantee the reliability of the weld in this material, plates of UNS S32304 with a thickness of 1.8 mm were welded by autogenous GTAW process with pulsed current with direct polarity, shieldinggaswith a mixture of argon and 2% of nitrogen and an automatic drive system with digital control of the parameters.The specimens were heat treated for 8 h at 600, 650, 700 and 750 ° C in a programmable muffle furnace, with accuracy of ± 5 ° C followed by air cooling.The sampleswere submitted to stress tests in the thermal-mechanical simulator using Gleeble®model 3500 and 3800 in the Brazilian Nanotechnology National Laboratory and Brazilian Synchrotron Light Laboratory, located at the Brazilian Center for Research in Energy and Materials. Hardness measurements were made the Vickers microhardness test with load of 1006 gf for the profile and loads of 1 and 2 gf for phase individual analysis. The microstructural characterization was done stereoscopy, optical microscopy and scanning electron microscopy. Phase quantification was performed by image processing and analysis using the FIJI -ImageJ and SVRNA software. It was verified that the increase of the heat treatment temperature promoted the increase in the content of the austenitic phase and consequently the increase of the ductility, increase of the hardening coefficient, reduction of the hardness and reduction of the mechanical strength